Poverty and Shared Prosperity Implications of Deep Integration in Eastern and Southern Africa - Balistreri, Edward J.; Maliszewska, Maryla; Osorio-Rodarte, Israel; Tarr, David G.; Yonezawa, Hidemichi (World Bank, Washington, DC, 2016)
Evidence indicates that trade costs are a much more substantial barrier to trade than tariffs are, especially in Sub-Saharan Africa. This paper decomposes trade costs into: (i) trade facilitation, (ii) non-tariff barriers, and (iii) the costs of business services. The paper assesses the poverty and shared prosperity impacts of deep integration to reduce these three types of trade costs in: (i) the East African Customs Union–Common Market of East and Southern Africa–South African Development Community "Tripartite" Free Trade Area; (ii) within the East African Customs Union; and (iii) unilaterally by the East African Customs Union. The analysis employs an innovative, multi-region computable general equilibrium model to estimate the changes in the macroeconomic variables that impact poverty and shared prosperity. The model estimates are used in the Global Income Distribution Dynamics microsimulation model to obtain assessments of the changes in the poverty headcount and shared prosperity for each of the simulations for the six African regions or countries. The paper finds that these reforms are pro-poor. There are significant reductions in the poverty headcount and the percentage of the population living in poverty for all six of the African regions from deep integration in the Tripartite Free Trade Area or comparable unilateral reforms by the East African Customs Union. Further, the incomes of the bottom 40 percent of the populations noticeably increase in all countries or regions that are engaged in the trade reforms. The reason for the poor share in prosperity is the fact that the reforms increase unskilled wages faster than the rewards of other factors of production, as the reforms tend to favor agriculture. Despite the uniform increases in income for the poorest 40 percent, there are some cases where the share of income captured by the poorest 40 percent of the population decreases. The estimated gains vary considerably across countries and reforms. Thus, countries would have an interest in negotiating for different reforms in different agreements.